Synopsis of Oryssomini Gordon (Coleoptera: Coccinellidae) from the Neotropical region with new species of Oryssomus Mulsant, Pseudoryssomus Gordon and Gordonoryssomus Almeida & Lima - Almeida, Lúcia M.; Santos, Paula B. (Zootaxa, 2014)
Six new species of Oryssomus are described: O. calix sp. nov., O. guillermo sp. nov., O. guyanensis sp. nov. and O. rhombus sp. nov., from French Guiana; and O. paschoali sp. nov. and O. rogeri sp. nov., from Brazil. Four new species of Pseudoryssomus are described: P. brulei sp. nov., P. crucifer sp. nov., P. triangulus sp. nov., from French Guiana; and P. rufomarginatus sp. nov., from Trinidad and Tobago. Three new species of Gordonoryssomus are described: G. mirnae sp. nov., from Peru, G. everardoi sp. nov. and G. limeirai sp. nov., from Brazil. The new species are placed within the South American classification of Gordon (1974) and Almeida & Lima (1995). Keys to genera and species of Oryssomus, Pseudoryssomus and Gordonoryssomus are included. Distribution maps and a checklist of the known species of Oryssomini are provided.